Delivery or desirability of benefits? Predicting the effectiveness of egoistic and altruistic message appeals for recycled water use. Issue 2 (3rd April 2022) - Posetti, Ben; Hurlimann, Anna; Tkaczynski, Aaron; Randle, Melanie; Dolnicar, Sara
ABSTRACT: A large proportion of the global population is currently grappling with water shortages. In many countries, the potential implementation of recycled water initiatives has been thwarted because of public opposition towards the notion of using recycled water. The development of effective advertising messages that increase public acceptance and willingness to use alternative water sources would increase the likelihood of recycled water use being embraced by communities. The present study conducted a factorial design experiment to test the effectiveness of 18 different print advertising messages in the context of recycled water use. Both egoistic and altruistic benefits are equally effective in increasing behavioural intention. Communicating the delivery rather than the desirability of benefits is more likely to increase community acceptance of recycled water. Print media represents a cost-effective marketing channel and has the potential to facilitate greater public support for recycled water initiatives.